ADAPTATION OF A BIOMARKER-BASED SEPSIS MORTALITY RISK STRATIFICATION TOOL FOR PEDIATRIC ACUTE RESPIRATORY DISTRESS SYNDROME - Yehya, Nadir (Crit Care Med, 2018)
OBJECTIVE: The original Pediatric Sepsis Biomarker Risk Model (PERSEVERE) and revised (PERSEVERE-II) biomarker-based risk prediction models have demonstrated utility for estimating baseline 28-day mortality risk in pediatric sepsis. Given the paucity of prediction tools in pediatric acute respiratory distress syndrome (ARDS), and given the overlapping pathophysiology between sepsis and ARDS, we tested the utility of PERSEVERE and PERSEVERE-II for mortality prediction in a cohort of pediatric ARDS, with an a priori plan to revise the model if these existing models performed poorly. DESIGN: Prospective observational cohort study. SETTING: University affiliated pediatric intensive care unit. PATIENTS: Mechanically ventilated children with ARDS. INTERVENTIONS: Blood collection within 24 hours of ARDS onset and biomarker measurements. MEASUREMENTS AND MAIN RESULTS: In 152 children with ARDS, PERSEVERE performed poorly and PERSEVERE-II performed modestly (areas under receiver operating characteristic curve of 0.61 and 0.76, respectively). Therefore, we randomly selected 80% of the cohort (n = 122) to re-derive a risk prediction model for pediatric ARDS (PARDSEVERE). We used classification and regression tree methodology, considering the PERSEVERE biomarkers in addition to variables relevant to ARDS. The final model was comprised of 3 biomarkers and age, and more accurately estimated baseline mortality risk (area under receiver operating characteristic curve 0.85, p < 0.001 and p = 0.053 compared with PERSEVERE and PERSEVERE-II, respectively). The model was tested in the remaining 20% of subjects (n = 30), and demonstrated similar test characteristics. CONCLUSION: A validated, biomarker-based risk stratification tool designed for pediatric sepsis was adapted for use in pediatric ARDS. The newly derived PARDSEVERE demonstrates good test characteristics internally, and requires external validation in a larger cohort. Tools such as PARDSEVERE have the potential to provide improved risk stratification and prognostic enrichment for future trials in pediatric ARDS.